Monitoring air pollution in real time using XML a reliable and cost-effective open source solution. - Blatnik, Stanko (XML journal :the ultimate enterprise resource.)
A few years ago there was no indication that XML could play an important role in computer-based process control. However, fast development and the spread of XML to different fields and emerging trends in the field of automation, have changed the situation tremendously.